Optimization of Twice-exceptional Students’ Giftedness in Memorizing the Qur'an - Wahab, Rochmat; Hermanto, Hermanto; Pamungkas, Bayu; Damayanto, Angga (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This study aims to describe the teachers’ efforts to optimize the giftedness of twice-exceptional students in memorizing the Qur'an. Design/methods/approach – The method used in this study was qualitative research with observation, interviews, and documentation as data collection techniques. Respondents in this study consist of 50 teachers of twice-exceptional students selected by random sampling. The data was then analysed through data condensation, data presentation, and drawing conclusions. Findings – The optimization of twice-exceptional students to memorize the Qur'an is shown by an assessment, direction of learning, and memorizing programs of the Qur'an according to their specificity, involvement in socio-religious activities in the community, and cooperation with the family. Research implications/limitations – This study was conducted in Yogyakarta City with teachers of twice-exceptional students as the respondents in the categories of gifted students with visual impairments, gifted students with hearing impairments, gifted students with physical barriers, and gifted students with autism. Originality/value – The development of Qur'an learning models for twice-exceptional students on different types of specificities needs to be enhanced to accommodate their specific abilities and needs.